Film Theories in Latin America and Research Policies - Zavala, Lauro (Comunicación y Medios, 2011)
In this paper I explore the conditions and consequences of the isolation of film scholarship in Latin American universities. This isolation is threefold: (1) internal isolation between the countries of the region, not only in the distribution of films in any format, but mostly a bibliographic isolation between researchers, books, and scholarly journals between these countries; (2) external isolation between Latin American scholars and colleagues in English-speaking countries (U.S, Canada, and England), and therefore an isolation of a very strong didactic and casuistic tradition in scholarly research, teaching, and formation of researchers; and (3) professional isolation between humanistic research on film and the research in social sciences (where the latter is over 90% of all film research projects in the region). In the last section of the paper I point out some strategies that might counterbalance this general situation.